1968
DOI: 10.1017/s0043174500047883
|View full text |Cite
|
Sign up to set email alerts
|

Competition of Wild Oat in Wheat and Barley

Abstract: Wild oat (Avena fatua L.) competition increased the losses in yield of both wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.) with increased densities of seedlings. At Fargo in 1965, wild oat densities of 70 and 160 seedlings/sq yd reduced the wheat yield 22.1% and 39.1%, respectively, compared to the wild oat-free check. Similar wild oat densities reduced the barley yield 6.5% and 25.9%, respectively. The addition of nitrogen and phosphorus fertilizer reduced the yield loss caused by wild oat 2 out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 8 publications
1
52
1
Order By: Relevance
“…The impact of an increase in UV-B radiation may not be important in natural communities where plant competition has little effect upon such community properties. However, the impact of UV-B radiation upon agricultural communities could have serious consequences since harvest yield quantity and quality are often influenced by interactions with weedy species (Bell andNalewaja 1968, McWhorter andPatterson 1980),…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of an increase in UV-B radiation may not be important in natural communities where plant competition has little effect upon such community properties. However, the impact of UV-B radiation upon agricultural communities could have serious consequences since harvest yield quantity and quality are often influenced by interactions with weedy species (Bell andNalewaja 1968, McWhorter andPatterson 1980),…”
Section: Discussionmentioning
confidence: 99%
“…The existence and importance of interspecific competition is well documented in agricultural situations. Bell and Nalewaja (1968) and Henson and Jordan (1982) have shown that significant decreases in wheat and barley yieids occur in the presence of wild oat. McWhorter and Patterson (1980) reviewed many studies that show reductions in soybean yields as a result of the presence of weeds.…”
Section: Interspecific Competitionmentioning
confidence: 99%
“…Wild oat is a common competitor of wheat and can substantially reduce wheat yield (Bell & Nalewaja, 1968). These species are similar in height and overall growth form.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the good fit produced by model 7, coefficients for GSP and nitrogen rate were negative, implying, counterintuitively, that these treatments had negative influences on wheat yield. Model 7 has the disadvantage that it does not draw upon decades of agronomic research that have established first principle nonlinear responses of wheat yield to the five variables studied here (Bell and Nalewaja 1968;Bowden and Friesen 1967;Martin et al 1987;O'Donovan et al 1985O'Donovan et al , 2005Wilson and Peters 1982). In contrast, model 5, the second-best-fitting model, did include underlying nonlinear yield responses with parameters that are of the correct sign, such as an estimate of the initial rate of yield increase as crop density increases from zero, an estimate of the initial rate of yield loss as weed density increases from zero, and the asymptote for maximum proportional yield loss as weed density increases.…”
Section: Modelmentioning
confidence: 99%